Impact of Nitrogen and Glycine Betaine on Winter and Spring Performance of Zoysiagrass - Mert Çakır; Songül Sever Mutlu (BioResources)
Zoysiagrass (Zoysia japonica Steud.) is a widely planted warm-season turfgrass; however, its long winter dormancy limits broader adoption, especially in transitional and subtropical regions. Glycine betaine (GB) is known to mitigate cold stress in controlled environments, but its potential to improve chilling tolerance of zoysiagrass as measured by winter color retention under field conditions remains unclear. This study investigated the effects of fall-applied GB and nitrogen (N) on winter color and spring green-up of zoysiagrass under field conditions in a Mediterranean climate in Türkiye. Conducted from 2018 to 2020 in Antalya, the experiment tested different application levels of N (0, 2.5, and 5 g/m²) and GB (0, 0.8, and 1.6 g/m²). N applications significantly improved key parameters, such as winter color retention, turf quality, chlorophyll content, and spring green-up. The highest N (5 g/m²) extended the green period from 7 to 10 months by delaying dormancy. In contrast, GB treatments had no significant effects. Although GB showed limited effectiveness, its evaluation under field conditions provides valuable insight into its practical relevance for warm-season turf management. The limited effect may be related to application amount and application timing. Further research with a broader range of GB application rates may help uncover its full potential under chilling stress conditions.